Clinical Uses of Intrathecal Therapy and Its Placement in the Pain Care Algorithm. Issue 8 (23rd February 2016) - Pope, Jason E.; Deer, Timothy R.; Bruel, Brian M.; Falowski, Steven
Abstract: Intrathecal drug delivery is an effective treatment option for patients with severe chronic pain who have not obtained adequate analgesia from more conservative therapies (eg, physical therapy, systemic opioids, nonsteroidal anti‐inflammatory drugs, antidepressants, and anticonvulsants). This review focuses on, but is not limited to, the 2 agents currently approved by the U.S. Food and Drug Administration for intrathecal analgesia: preservative‐free morphine and ziconotide (a nonopioid, selective N‐type calcium channel blocker). We describe the appropriate use of intrathecal therapy in the management of severe chronic pain, based on current best practices. Topics addressed here include patient selection, trialing, dosing and titration, adverse event profiles, long‐term management, intrathecal therapy for cancer‐related pain, and the placement of intrathecal therapy in the pain care algorithm. In appropriately selected patients with chronic pain, intrathecal therapy can provide substantial pain relief with improved functioning and quality of life. Successful long‐term management requires ongoing patient monitoring for changes in efficacy and the occurrence of adverse events, with subsequent changes in intrathecal dosing and titration, the addition of adjuvant intrathecal agents, and the use of concomitant oral medications to address side effects, as needed. Based on an infrequent but clinically concerning risk of overdose, granuloma, and other opioid‐induced complications, nonopioid therapy with ziconotide may be preferred as a first‐line intrathecal therapy in patients without a history of psychosis or allergy.